Training and technical backstopping in the use of RiceAdvice technology - Guindo, Samuel; Dossou-Yovo, Elliott Ronald (Accelerating Impacts of CGIAR Climate Research for Africa, 2021)
RiceAdvice is a free android-based application that provides farm-specific advice on rice management practices particularly on crop calendar construction to avoid climatic stresses and site-specific fertilizer recommendations to increase fertilizer use efficiency, crop yield and farmers income while reducing greenhouse gas emission and nitrate leaching. From the prioritization workshop, RiceAvice received the highest score in terms of both the climate smart performance indicator (increase in yield and resilience and reduction in greenhouse gas emission), gender inclusivity, technical feasibility, cost for implementation and demand by farmers, and was therefore selected as one of the most relevant CSA technologies in Mali. Due to the limited technical capacity in Mali in the operation of RiceAdvice, the project organized training sessions and provided technical backstopping to the young service providers of the Center for Mechanized Agriculture (CEMA). The CEMA provides mechanized land preparation, harvesting and paddy storage services. They are available to farmers' organization members and independent farmers. Today, more than 300,000 farmers are members of the CEMA in Mali. The AICCRA project uses the CEMA as an entry point in Mali for piloting and scaling CSA and CIS technologies because they are financially autonomous and can continue the scaling the technologies after the project ends. The Training, co-organized by the Syngenta Foundation for Sustainable Agriculture and Africa Rice Center (AfricaRice), was held on 10 – 11 June 2021 at the Segou office, Mali. There was in total 21 participants, including 6 female from five CEMA. This report summarizes the main activities conducted during the training sessions.